Assessment of seismic risks in code conforming reinforced concrete frames. (1st September 2015) - Shokrabadi, Mehrdad; Banazadeh, Mehdi; Shokrabadi, Mehran; Mellati, Afshin
Highlights: The seismic performance evaluation steps of FEMA P-58 have been applied to 15 RC frames. The collapse risk and human and monetary consequences have been evaluated. The effects of ductility, seismicity, height and redundancy have been investigated. A thorough discussion on the reasons of variations is provided. Abstract: The main objective of this study is to employ performance-based earthquake engineering procedure to evaluate earthquake-induced risks in modern code-conforming reinforced (RC) concrete moment frames in terms of collapse risk and possible human and financial losses. A set of 30 archetype RC moment frames, designed based on the ASCE 7-05 and ACI 318-05 requirements, is selected for the evaluation purpose. The buildings are classified into 4-, 8- and 12-story and are designed with different levels of structural system ductility. The archetypes are assumed to be located in three zones with low, moderate and high levels of seismic hazard. The findings of the collapse assessment procedure indicate that the seismicity of the location significantly affects the collapse performance and the ductility, as long as the structure conforms to the requirements of modern design codes, has the least influence on the collapse risk. Also, it has been found that the expected annual repair costs lie in an interval with the minimum and maximum of 0.02% and 1.5% of the replacement cost and expected annual number of deaths ranges from 2 × 10 −4 % to 29 × 10 −3 % of the total occupants with the buildings located in the low seismicity zone having the minimum amounts of losses. Sensitivity analysis is employed to study the variations of earthquake consequences due to the variations in the design decisions.